Economic development in a globalized environment : East Asian evidences - Wan, Henry Y. (Norwell, Mass. : Kluwer Academic Publishers, 2004)
"Economic Development in a Globalized Environment: East Asian Evidences scrutinizes the major debates in development economics, using documented cases, and analytic reasoning for support. Instead of the simplistic North-vs-South view, it further explains international technology transfer in a tripartite relationship of the North-North rivalry, the South-South competition and the North-South alliance. Case studies, statistical series and analytical model are deployed to set forth the reasoning."--BOOK JACKET.
Pt. 1. General Considerations -- Ch. 1. Introduction -- Ch. 2. Replicable Cases? -- Ch. 3. Conditions for Sustained Growth -- Ch. 4. Channels for Technology Acquisition -- Ch. 5. Major Debates in Economic Development -- Ch. 6. Crisis amidst Growth -- Pt. 2. Economy-Specific Evidence -- Ch. 7. The Republic of Korea -- Ch. 8. Taiwan -- Ch. 9. Hong Kong -- Ch. 10. Singapore -- Ch. 11. Outward Oriented Development Elsewhere -- Ch. 12. Conclusions.
Includes bibliographical references (p. 361-372) and indexes.
Keywords: Globalization -- Economic aspects -- East Asia -- Case studies; Economic development -- Case studies; East Asia -- Economic conditions -- Case studies; East Asia -- Foreign economic relations -- Case studies